2014
DOI: 10.1002/lary.24966
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of sialendoscopy, sonography, and CBCT in the detection of sialolithiasis

Abstract: 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
57
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 12 publications
2
57
1
1
Order By: Relevance
“…In consistency with the results of this study, the authors emphasized that the size of the stones was decisive for the false‐negative rate, with significantly higher sensitivity for stones starting from 3 mm in size . Schwarz et al conducted a retrospective study of 43 patients to compare sonography, cone beam CT, and sialoendoscopy as diagnostic procedures. The study showed that sonography had sensitivity of 73%, specificity of 90%, a PPV of 96%, and an NPV of 47%.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…In consistency with the results of this study, the authors emphasized that the size of the stones was decisive for the false‐negative rate, with significantly higher sensitivity for stones starting from 3 mm in size . Schwarz et al conducted a retrospective study of 43 patients to compare sonography, cone beam CT, and sialoendoscopy as diagnostic procedures. The study showed that sonography had sensitivity of 73%, specificity of 90%, a PPV of 96%, and an NPV of 47%.…”
Section: Discussionsupporting
confidence: 79%
“…Interestingly, the authors also found that cone beam CT did not provide significantly better imaging of these concrements, which had a false‐negative rate of 36.4% (4 of 11). Furthermore, there was no distinction made between the submandibular and parotid glands . In a case series including 24 patients, Jäger et al reported both sensitivity and specificity rates of 80% for diagnosing sialolithiasis in the submandibular gland using sonography in comparison with sialography.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After clinical examination, ultrasound is recommended as a primary diagnostic tool [4,5]. However, imaging tools can miss small salivary stones, and also have difficulty in detecting other duct pathologies (e.g., stenoses) which might then show up in sialendoscopy [6,7].…”
Section: Introductionmentioning
confidence: 99%